2008
DOI: 10.1016/j.ijgo.2008.10.020
|View full text |Cite
|
Sign up to set email alerts
|

Group B streptococcus colonization among pregnant women in Uruguay

Abstract: SynopsisThe prevalence of group B streptococcus colonization in pregnant women was 17.3% in the largest maternity hospital in Uruguay. KeywordsColonization; Group B streptococcus; Pregnant women; Uruguay Group B streptococcus (GBS) is one of the most common causes of neonatal sepsis. In the United States, 5%-10% of neonatal deaths are caused by this organism [1]. Early-onset GBS disease is defined as an infection occurring in the first week of life and accounts for approximately 70% of all GBS diseases in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 3 publications
1
1
0
3
Order By: Relevance
“…These values are similar to that reported by Oviedo et al (2013) (9.38%) using swab samples taken from the same study population, The average prevalence reported in South America is 15.90% [36]. Several studies in bordering countries reported similar colonization rates: in Brazil values from 4.20 to 28.40% [37]; in Chile, 19.80% [38]; and in Uruguay, 17.30% [39]. In Mexico, a literature review study found a 9.50% maternal colonization [40].…”
Section: Discussion Colonization In Full-term Pregnant Womensupporting
confidence: 90%
“…These values are similar to that reported by Oviedo et al (2013) (9.38%) using swab samples taken from the same study population, The average prevalence reported in South America is 15.90% [36]. Several studies in bordering countries reported similar colonization rates: in Brazil values from 4.20 to 28.40% [37]; in Chile, 19.80% [38]; and in Uruguay, 17.30% [39]. In Mexico, a literature review study found a 9.50% maternal colonization [40].…”
Section: Discussion Colonization In Full-term Pregnant Womensupporting
confidence: 90%
“…Several studies of countries bordering Argentina have reported similar colonization rates: Chile, 19.8% (Abarzua et al , 2002); Uruguay, 17.3% (Laufer et al , 2009) and Brazil, 14.6% (Simões et al , 2007). …”
Section: Discussionmentioning
confidence: 80%
“…9 Otro trabajo llevado a cabo en la Clínica Colombia de Bogotá en 2008 estableció un 16,4% de prevalencia a partir de cultivo vaginorrectal y un 1,7% de cultivo vaginal, sin embargo, no identificaron los serotipos ni el perfil de susceptibilidad antimicrobiana en las muestras estudiadas. 22 En cuanto a la resistencia antibiótica del Streptococcus agalactiae en el estudio antes mencionado, se reporta una resistencia del 16,7% de las cepas. 9 Nuestro estudio es el primero en tipificar las cepas de Streptococcus agalactiae en la población usuaria del Hospital Militar Central.…”
Section: Discussionunclassified
“…Hay controversia sobre la prevalencia de este germen en el ámbito latinoamericano, debido a la gran variabilidad en la información disponible. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] Se requieren datos locales de prevalencia para determinar la magnitud del fenómeno. Por este motivo, el grupo decidió realizar un estudio con el objetivo de estimar la prevalencia de este patógeno en las maternas que acuden diariamente al Hospital Militar Central en Bogotá (Colombia), identificar los serotipos y así establecer aquellos que circulan en nuestra población y la resistencia asociada.…”
Section: Introductionunclassified